Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10140-007-0651-8
|View full text |Cite
|
Sign up to set email alerts
|

Blunt traumatic injuries of the lung parenchyma, pleura, thoracic wall, and intrathoracic airways: multidetector computer tomography imaging findings

Abstract: This pictorial review discusses multi-detector computed tomography (MDCT) cases of non-vascular traumatic chest injuries, with a brief clinical and epidemiological background of each of the pathology. The purpose of this review is to familiarize the reader with common and rare imaging patterns of chest trauma and substantiate the advantages of MDCT as a screening and comprehensive technique for the evaluation of these patients. Images from a level 1 trauma center were reviewed to illustrate these pathologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 30 publications
1
87
0
5
Order By: Relevance
“…As the omentum is flexible and mobile abdominal structure, it might initiate a herniation into the thorax [34]. It has been reported that the diagnosis of TDI may be missed in 30% of cases on initial CT scanning [35]. Affected patients are typically showed severe multi-organ injures that may dominate and mask the presentation of TDI.…”
Section: Discussionmentioning
confidence: 99%
“…As the omentum is flexible and mobile abdominal structure, it might initiate a herniation into the thorax [34]. It has been reported that the diagnosis of TDI may be missed in 30% of cases on initial CT scanning [35]. Affected patients are typically showed severe multi-organ injures that may dominate and mask the presentation of TDI.…”
Section: Discussionmentioning
confidence: 99%
“…These fractures are rarely life threatening by themselves, but can be an external indicator of more severe visceral injury inside the abdomen and chest [2,4,5,15]. The most common mechanism of injury for rib fractures in the elderly is a fall from a height or standing.…”
Section: Discussionmentioning
confidence: 99%
“…From the comparison of virtopsy and autopsy, we noticed that the presence of fluid in the paranasal sinuses was not noticed during the autopsy. The only patient without fluid in the paranasal sinuses, and who had died in 2005 after the air crash, had cerebral oedema with subarachnoid and intraventricular haemorrhage, cerebral venous congestion, multiple bone fractures in the head (fracture of the orbital floor with orbital emphysema and herniation of the inferior rectus muscle), in the chest (multiple rib fractures) and in the pelvis (fracture of the sacrum and of the acetabular edge with haemarthrosis); moreover, this patient showed haemothorax seen as the ''haematocrit sign'' [13], pneumomediastinum and air in the heart chambers, aorta, pulmonary artery and its lobar branches, descending thoracic aorta and in the arterial and venous splanchnic vessels.…”
Section: Resultsmentioning
confidence: 92%